Deconstructive Nature of Pedagogy In Virginia Woolf With Special Reference to a Room of One’S Own: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Amongmany aspects of feminism, one that has generally been overlooked is the natureof pedagogic dimension inherent in each feminist text. The paper aims atfinding this dimension in Virginia Woolf’s ARoom of One’s Own, particularly the deconstructive nature of pedagogy.